Severance Pay Compliance in Indonesia - Brusentsev, Vera; Newhouse, David; Vroman, Wayne (2012)
This paper contributes new evidence from two large household surveys on the compliance of firms with severance pay regulations in Indonesia, and the extent to which changes in severance pay regulations could affect employment rigidity. Compliance appears to be low, as only one-third of workers entitled to severance pay report receiving it, and on average workers only collect 40 percent of the payment due to them. Eligible female and low-wage workers are least likely to report receiving payments. Widespread non-compliance is consistent with trends in employment rigidity, which remained essentially unchanged following the large increases in severance mandated by the 2003 law. These results suggest that workers may benefit from a compromise that relaxes severance pay regulations while improving enforcement of severance pay statutes, and possibly establishing a system of unemployment benefits.